Long Non-Coding RNAs: New Players in Hematopoiesis and Leukemia - Morlando, Mariangela; Ballarino, Monica; Fatica, Alessandro (Frontiers in Medicine, 2015)
Long non-coding RNAs (lncRNAs) are important regulators of gene expression that influence almost every step in the life cycle of genes, from transcription to mRNA splicing, RNA decay, and translation. Besides their participation to normal physiology, lncRNA expression and function has been already associated to cancer development and progression. Here, we review the functional role and mechanisms of action of lncRNAs in normal hematopoiesis and how their misregulation may be implicated in the development of blood cell cancer, such as leukemia.